Surgical management of tuberculum sellae meningiomas: involvement of the optic canal and visual outcome - Schick, U (BMJ Group, 2005)
Objective: To present a large series of surgically treated tuberculum sellae meningiomas with particular regard to involvement of the optic canal and visual outcome. Methods: A retrospective analysis was done on 53 patients (40 female) with meningiomas originating from the tuberculum sellae who underwent surgery between 1991 and 2002. The standard surgical approach consisted of pterional craniotomy. Sixteen meningiomas extended posteriorly onto the diaphragma sella, 29 anteriorly to the planum sphenoidale, and 19 to the anterior clinoid process. Thirty seven tumours involved the optic canal, three bilaterally. Follow up ranged from 6 to 108 months (mean 29.9 months). Results: Total macroscopic resection was achieved in 48 patients. Median tumour size was 2.6 cm. Postoperatively, visual acuity improved in 20 patients and deteriorated in seven. Preoperative and postoperative visual acuity worsened with increasing duration of preoperative symptoms and with increasing age. Extension into the intraconal space was a negative predictor. However, tumour size did not influence visual acuity. Recurrence occurred in two cases (21 and 69 months postoperatively). Two patients died from causes unrelated to the tumour. Conclusions: In the majority of patients with tuberculum sellae meningiomas, total resection may be achieved through a pterional approach with minimal complications.